Teaching English in Non-English Departments: Empowering Teacher Towards Improvement - Ninuk Sholikhah Akhiroh (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT English Language Teaching (ELT) in non-English majors already has its “home” but not its “host”. It means that the parties involved in the teaching have not been able to manage an effective ELT yet. There could be many aspects related to this, yet this paper prefers to propose a solution to improve the effectiveness of English teaching in non-English majors by empowering the English language lecturer. This paper refers to the results of research conducted on the teaching of English in the Faculty of Social Sciences that use lecturers and students as the main informant, as well as interviews, observation and document analysis as data collection techniques. The results showed that some important improvement in ELT for non-English majors can be initiated by the lecturers. There are some necessary steps to do to reinforce the role of lecturers in ELT implementation. They are involving the lecturer in designing or revising the curriculum, building connection with fellow ESP lecturers and lecturers of relevant field of study, and activating Focus Group Discussion among teaching team. These steps hopefully will be complemented by the improvement of other aspects in ELT for non-English departments to build an effective teaching. ABSTRAK Pengajaran bahasa Inggris di jurusan non-bahasa Inggris baru memiliki “rumah” saja, belum “tuan rumah”nya. Ini berarti bahwa pihak-pihak yang terlibat dalam pembelajaran belum dapat menata sebuah pengajaran bahasa Inggris yang efektif. Ada banyak hal yang dapat dilakukan, namun tulisan ini memilih untuk mengajukan sebuah solusi perbaikan pengajaran bahasa Inggris di jurusan non-bahasa Inggris dengan cara memberdayakan dosen pengampu matakuliah. Tulisan ini merujuk pada hasil penelitian yang dilakukan terhadap pengajaran bahasa Inggris di Fakultas Ilmu Sosial dengan menggunakan dosen dan mahasiswa sebagai informan utama, serta wawancara, observasi dan analisis dokumen sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa beberapa perbaikan penting dalam penegajaran bahasa Inggris dapat difasilitasi oleh dosen pengampu matakuliah. Langkah-langkah yang dapat dilakukan adalah: melibatkan dosen dalam menyusun kurikulum pengajaran bahasa Inggris; membangun hubungan dengan sesama dosen pengajar ESP dan dosen ahli bidang ilmu tertentu; mengaktifkan forum diskusi antar anggota tim pengajar. Langkah-langkah ini diharapkan dapat dilengkapi dengan perbaikan dari aspek-aspek lain guna mewujudkan pembelajaran yang efektif. How to Cite: Akhiroh, N. S. . (2017). Teaching English in Non-English Departments: Empowering Teacher Towards Improvement. IJEE (Indonesian Journal of English Education), 4(1), 49-62. doi:10.15408/ijee.v4i1.5341